Digital Technology-Based Green Innovation Adoption Model in MSME Development to Promote Performance and Sustainable Business Competitiveness - Agusman Agusman; Victor Victor; Silvia Sofyan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study empirically examines the direct effects of green innovation adoption and digital technology utilization on MSME performance and sustainable business competitiveness, as well as the effect of MSME performance on sustainable business competitiveness, in the context of MSMEs in Medan, Indonesia. Method. A quantitative, cross-sectional survey design was employed. Primary data were collected from 100 MSMEs, selected by purposive sampling from a population of 18,000 active units using the Slovin formula, through a structured questionnaire. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) in SmartPLS 4, including outer model evaluation (loading factor, AVE, composite reliability, Cronbach's alpha, discriminant validity) and inner model evaluation (R², f²). Main Findings. All measurement constructs met the required thresholds, confirming convergent validity, discriminant validity, and reliability. The structural model shows that Sustainable Business Competitiveness is explained by the exogenous variables with R² = 0.385, while MSME Performance is explained with R² = 0.295. Green Innovation and Digital Technology exert a moderate effect on Sustainable Business Competitiveness (f² = 0.218 and f² = 0.192, respectively), while their direct effect on MSME Performance is very small (f² = 0.002 and f² = 0.006). MSME Performance, in turn, shows a moderate effect on Sustainable Business Competitiveness (f² = 0.194). Practical Implications. The findings inform MSME owners, business incubators, MSME facilitators, and digital platform providers that green innovation initiatives yield stronger competitiveness gains when embedded within a broader digital transformation strategy. For policy makers, particularly the Ministry of Cooperatives and SMEs, the results support targeted programs on digital literacy, eco-innovation subsidies, and integrated capacity-building schemes for second-tier city MSMEs. Originality. This study contributes an integrated, empirically validated model that combines digital technology utilization and green innovation adoption as joint predictors of MSME performance and sustainable competitiveness, tested through SEM-PLS on Indonesian MSMEs a setting under-represented in the existing Q1/Q2 literature.